The geography of the Tsimshian Indians [electronic resource] - Dorsey, George A. (George Amos), 1868-1931 ([Chicago? : s.n., 1897)
Caption title. "Reproduced from The American antiquarian, October, 1897." -p. [1]. Electronic reproduction. Mode of access: Internet. 44